Henry James and the father question - Taylor, Andrew, 1968- (Cambridge studies in American literature and culture, 2002)
"The intellectual relationship between Henry James and his father, who was a philosopher and theologian, proved to be an influential resource for the novelist. Andrew Taylor explores how James's writing responds to James Senior's epistemological, thematic and narrative concerns, and relocates these concerns in a more secularised and cosmopolitan cultural milieu. Taylor examines the nature of both men's engagement with autobiographical strategies, issues of gender reform, and the language of religion. He argues for a reading of Henry James that is informed by an awareness of paternal inheritance. Taylor's study reveals the complex and at times antagonistic dialogue between the elder James and his peers, particularly Emerson and Whitman, in the vanguard of mid nineteenth-century American Romanticism. Through close readings of a wide range of novels and texts, he demonstrates how this dialogue anticipates James's own theories of fiction and selfhood."--Jacket